Krakow : an ecobiography - Izdebski, Adam; Szmytka, Rafał (2021)
Chapter 1: The climate history of Krakow / Konrad Wnęk, Adam Izdebski, and Leszek Kowanetz – Chapter 2: Krakow and its rivers / Andrzej Chwalba, with a contribution by Konrad Wnęk – Chapter 3: Plants in the lives of medieval Cracovians / Aldona Mueller-Bieniek – Chapter 4: A city Is not an island: early modern Kraków and natural resources / Piotr Miodunka – Chapter 5: Pollution in early modern Krakow / Rafał Szmytka – Chapter 6: Industrialization: the environmental end of Old Krakow? / Ewelina Szpak – Chapter 7: The history of Krakow smog / Adam Izdebski and Konrad Wnęk – Chapter 8: The power of myth: the imagined nature of Krakow / Małgorzata Praczyk